An analysis approach for micro gas turbine engine's performance by experiment and numerical simulation - Xiaohua Wu; Xiaoan Hu; Xin Xiang; Shengzhi Lin; Junjie You; Feiyu Tian (Case Studies in Thermal Engineering, 2023)
The corrected special maps of components have revealed an outstanding role on valuating the off-design performance of micro gas turbine engines. The main purpose of this paper is to investigate the steady-state performance at design and off-design point of a micro turbojet engine capable of generating 400 N thrust. At present work, the experiments were conducted and the thrust and specific fuel consumption are 39.48 daN and 1.62kg/(daN h) at design point, respectively. Importantly, a present methodology, that is adjusting the values of Beta and N/sqrt(T) in specific map of the components when performing the off-design calculation of this engine, is proposed in this research, where results are compared with the data from experiment and other literature. Exemplarily, according to a comparison with the experimental results, there is less than 1% of the deviation in thrust at design point and 3% of the difference in the thrust at off-design point with the corrected specific map when performing the numerical simulation. This method enables evaluating the operating characteristics of both on design and off-design point, providing more accurate trend analysis of performance parameters in terms of engine compared to the researches which seldom used the scaling map.